Financial Feasibility Study and Maintenance Strategy of Articulated Dump Truck (A Case Study of PT. KLM) - Fajar Ikhwan Rosyidi; Ahmad Danu Prasetyo (Journal of International Conference Proceedings, 2021)
Beyond 2021, the challenging difficulties would need coal mining firms, particularly PT.KLM, to increase operational efficiency. The author conducts a root cause analysis in order to determine one of the causes of the business's inefficiencies. At the time, one of PT. KLM's inefficiencies is a result of the articulated dump truck’s (ADT) performance, which fell short of the projected aim. The author provides two alternatives for ADT at PT. KLM, starting from Certified Rebuild Machine (CRM) then Full Maintenance Service (FMS) and CRM then Full Maintenance Contract (FMC). Feasibility studies are undertaken in order to determine the most viable alternative. Both sensitivity analysis and Monte Carlo simulation is conducted to determine the input variable's influence on changes in NPV (Net Present Value) and to generate a variety of possible outcomes and probabilities of various situations. The author proposes scenario 2 as the optimal scenario with the highest NPV based on the study. Additionally, following the Monte Carlo simulation, the mean NPV + minimum NPV and mean NPV + maximum NPV values for scenario 2 are the highest in comparison to the other scenario.